Taxonomic and geographic differentiation of Juniperus phoenicea agg. based on cone, seed, and needle characteristics. Issue 5 (4th July 2018) - Mazur, Małgorzata; Zielińska, Monika; Boratyńska, Krystyna; Romo, Angel; Salva-Catarineu, Montserrat; Marcysiak, Katarzyna; BoratyŃski, Adam
Abstract : The aim of this study was to examine the diversity of, and differentiation between, 41 natural populations representing Juniperus phoenicea complex within their geographic range using the morphological characteristics of cones, seeds, and sprouts with leaves. Seven populations of J . phoenicea s.s ., 25 J . turbinata and nine J. canariensis, each represented by ∼20–30 individuals, were studied. The characteristics describing the size of cones and seeds and their proportions were different between J. phoenicea s.s., J. turbinata, and J. canariensis, and were useful in distinguishing between these three taxa. The populations of J. canariensis had a significantly higher percentage of trimerous cones, a higher number of cone scales, but a lower number of seeds, which were also larger than the seeds from other taxa. Juniperus phoenicea s.s., J. turbinata, and J. canariensis revealed a high level of multivariate differentiation, but there were no single characteristics which allowed one to distinguish between these alone. We detected significant differences between populations of J. turbinata from Europe and Africa, which supports the role of the Gibraltar Straight in the structuring of conifer species. Significant differences were also detected between European and Asiatic populations in several characters examined, indicating the important role of the Aegean Sea in the structuring of this taxon.